Pengaruh Fasilitas Belajar, Lingkungan Keluarga, dan Keterampilan Guru Mengajar terhadap Minat Belajar - Rejeki, Atun Sri; Rozi, Fahrur (Jurusan Pendidikan Ekonomi, Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This study aims to determine the effect of learning facilities, family environment, and teacher skills in teaching on student interest in office administration at SMK PGRI 1 Mejobo Kudus. The population in this study were all students of class X, XI, and XII of the Office Administration Department of SMK PGRI 1 Mejobo Kudus, totaling 137 students with a sampling technique using saturated sampling, where all members of the population were used as research samples. The results of multiple linear regression analysis obtained the equation Y= 5.227 + 0.407 FB + 0.181 LK -0.065 KG + e. Test the significance of the regression equation with the F test, obtained F count = 43.691 with a significant value of 0.000 which means <0.05 which indicates that 1) Learning facilities, family environment, and teacher skills in teaching affect student learning interest by 36%, 2) Learning facilities have an effect on student learning interest by 19.45%, 3) Family environment affects student learning interest 12.04%, and 4) Teacher skills in teaching affect student learning interest by 4.16%. Based on the results of the study, it can be concluded that learning facilities, family environment, and teacher skills in teaching affect learning interest both simultaneously and partially. Future research is expected to be able to develop other independent variables that may affect interest in learning